Presupposition Processing- The Case of German wieder - Schwarz, Florian; Tiemann, Sonja (Proceedings of the Amsterdam Colloquium, 2011)
Presuppositions are vital for language comprehension, but little remains known about how they are processed. Using eye tracking in reading, we investigated two issues based on German wieder (’again’). First, we looked at the time course of presupposition processing by testing for processing costs of unsupported presuppositions. Secondly, we tested whether embedding wieder under negation affected a potential mismatch effect. Presupposition-induced effects showed up immediately after wieder, but only in the unembedded context, suggesting that embedding interferes with the detection of the mismatch. However, judg ments in a follow-up rating study indicate that a mismatch is perceived in both the embedded and unembedded conditions when the PSP is not supported by the context. Taken together, these results suggest that detection of the mismatch under embedding is delayed in processing.